Keeping it in the Family: The proposed and rejected Irish Constitutional amendment on family caregiving - Insights from the IDS-TILDA Carers Study (TARA Database) - Mc Carron, Mary; Brennan, Damien; Mc Callion, Philip (My University, 2025)
Background: In 2024, Irish people rejected their government's proposed Constitutional changes relating to the definition of a family, and the interface between state and family with reference to the provision of care. Using data from a Carer's Study, this paper reflects on the defeated Care Amendment with reference to current and historic social policy that mediates, shapes and informs family and the state's responsibility for care provision for people with intellectual disability. Methods: Family carers of older people with intellectual disability completed a self‐administered, mixed methods question- naire. Qualitative data were analysed thematically, and a descriptive analysis of the quantitative data was conducted using SPSS. Findings: The positioning of the family as the principal point of care is remarkably robust even in the face of personal challenges experienced by caregivers. Within the reality of limited formal services, it would appear that family‐based care continues to be constructed as the natural and neutral form of care provision, relieving the state of obligations to care for citizens with disabilities. Conclusions: An urgent exploration of the social contract for care is required to address the fundamental question as to where the responsibility for the long‐term care of people with intellectual disability resides.
PUBLISHED
Keywords: Ageing